Causes of excess mortality in diabetes patients without coronary artery disease. (3rd October 2022) - Olesen, K; Gyldenkerne, C; Thrane, P G; Maeng, M
Abstract: Background: Diabetes (DM) patients without coronary artery disease (CAD) by coronary angiography have a similar risk of myocardial infarction and cardiac death as non-DM patients without CAD. Yet, even with absence of CAD, patients with DM have higher mortality compared to non-DM patients. Aims: To examine the underlying causes of death in patients undergoing coronary angiography depending on DM and CAD. Methods: We included every patient with no previous history of CAD who underwent coronary angiography in Western Denmark between 2003–2016. Patients were stratified by DM and CAD and followed for a maximum of 10 years. We estimated the 10-year cumulative risk of all-cause death and cause-specific death. Causes of death were categorized as "cardiovascular", "pulmonary", "cancer", "renal", "bleeding-related", and "other" based on ICD-10 codes listed as underlying causes of death obtained from death certificates. Deaths where DM was listed as the underlying cause of death (i.e. ICD-10 code DE1) were included in the category "other". Results: We included 132, 432 patients, of whom 33% had neither DM nor CAD, 5% had DM only, 51% had CAD only, and 11% had both DM and CAD. Mean age was 64 years. Median follow-up was 6.3 year (inter-quartile range 3.8–10.0). During follow-up, 35, 036 (26.5%) patients died. Patients with both DM and CAD had the highest 10-year mortality (47.4%, 95% CI 46.3–48.4), followed by CAD only (33.3%, 95% CI 32.8–33.7), DM only (30.7%, 95% CI 29.3–32.2), and patients with neither DM nor CAD (21.6%, 95% CI 21.1–22.1). The proportion of cardiovascular deaths were similar in patients with DM only (29.2%, 95% CI 27.0–31.5, Figure) and patients with neither DM nor CAD (29.7%, 95% CI 28.8–30.7). Patients with DM were more likely to die from causes categorized as "other" compared to patients with neither DM nor CAD [38.4% (95% CI 36.0–40.9) versus 30.2% (95% CI 29.3–31.2)]. Among patients with DM only, 43.7% of deaths classified as "other" were attributable to DM-related complications such as ketoacidosis and diabetic nephropathy. Conclusion: Despite absence of CAD, DM remained associated with increased mortality. Excess mortality was primarily driven by patients dying of DM-related microvascular complications and ketoacidosis. Thus, despite absence of CAD, patients with DM require continued preventative measures to reduce DM-related mortality. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Aarhus University Hospital